Canagliflozin and Renal Outcomes in Type 2 Diabetes and Nephropathy - Perkovic, Vlado; Jardine, Meg J; Neal, Bruce; Bompoint, Severine; Heerspink, Hiddo J.L; Charytan, David M; Edwards, Robert; Agarwal, Rajiv; Bakris, George; Bull, Scott; Cannon, Christopher P; Capuano, George; et al. (The New England journal of medicine, 2019)
This double-blind, randomized trial compared canagliflozin with placebo in patients with type 2 diabetes and evidence of kidney disease that was treated with renin–angiotensin system blockade. The canagliflozin group had a lower risk of kidney disease progression or cardiovascular events than the placebo group.